Carpe diem - zagrabi dan - Ramšak, Mojca (Etnolog. Nova vrsta (Ljubljana), 2000)
The article outlines the life and work of Dr. Marija Makarovič. In the context of her remarkably extensive work the article presents the central themes of her activities in the field of ethnology: peasant costumes, health culture, farm economy, the social culture of the countryside, border settlements and vanishing settlements, life stories.
Keywords: Makarovič, Marija, 1930-; biografije; ethnology; etnologija; Slovenci; Slovenes